Multidisciplinary approach in the management of neurotrauma and its sequelae - Agrawal, Amit (Nepal Journal of Neuroscience, 2022)
It is well known that traumatic brain injury (TBI) can long-term consequences of major public health concern. It can be said that wide spectrum and distinct lesions resulting in variable clinical consequences make the process of post-TBI rehabilitation challenging. A patient who sustains TBI can have variable outcome ranging from complete recovery to persistent vegetative state. Between these two there is a spectrum of TBI related sequel which may be disturbed levels of consciousness, post-traumatic agitation, post-traumatic paroxysmal sympathetic hyperactivity, posttraumatic hydrocephalus, and posttraumatic neuroendocrine dysfunctions all these requiring different rehabilitation programmes and rehabilitation approaches.